Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Please can you explain me why

$$ \nabla^2 G_{\omega}(R) = f(R) $$

is equivalent to

$$ \frac{1}{R} \frac{d^2(RG_\omega(R))}{d R^2} = f(R) $$

Here:

  • $G_\omega(R)$ is the Fourier transform of $G$
  • $G$ is the Green's function
  • We suppose that $G$ and $f$ are spherically symmetric
  • $R = \sqrt{x^2 + y^2 + z^2}$

Thanks!

share|improve this question
add comment

1 Answer

up vote 3 down vote accepted

If $H(R)$ is spherically symmetric, we can write the Laplacian of $H$ in spherical coordinates:

$\nabla^2 H = \frac{1}{R^2}\frac{d}{dR}\bigg(R^2\frac{dH(R)}{dR}\bigg)$

(see wikipedia).

Then, $\frac{d}{dR}\bigg(R^2\frac{dH(R)}{dR}\bigg) = R^2\frac{d^2H}{dR^2} + 2R \frac{dH}{dR}$

On the other way, $\frac{d}{dR}(RH(R)) = R\frac{dH}{dR} + H$ and thus

$\frac{d^2}{dR^2}(RH(R)) = R\frac{d^2H}{dR^2} + 2\frac{dH}{dR}$

$\Rightarrow \frac{1}{R^2}\frac{d}{dR}\bigg(R\frac{dH(R)}{dR}\bigg) = \frac{1}{R}\frac{d^2}{dR^2}(RH(R))$

$\Rightarrow \nabla^2 H = \frac{1}{R^2}\frac{d}{dR}\bigg(R^2\frac{dH(R)}{dR}\bigg) = \frac{1}{R}\frac{d^2}{dR^2}(RH(R))$.

Now, apply it to $G_{\omega}$.

share|improve this answer
    
Thank you very much! –  Abramo Oct 29 '10 at 13:36
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.